Problems in Exposure Assessment of Fluoride in Drinking Water - Elise 6. Bassln, DMD, DMSc; Murray A. Mlttleman, MD, DrPH; David Wypij, PhD, Kaumudi Joshipura, BDS, (Blackwell Synergy, 2004)
We developed a source documentation approach that identified fluoride content of drinking water at the state or local level to estimate fluoride concentrations from public water systems.